2005
DOI: 10.1086/497025
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Kilohertz Quasi‐periodic Oscillations and Shifted Frequency Correlations in the Accreting Millisecond Pulsar XTE J1807−294

Abstract: We report the discovery of twin kilohertz quasi-periodic oscillations ( kHz QPOs) in the X-ray flux of XTE J1807À294, the fourth accreting millisecond pulsar (AMP). This is the second AMP exhibiting twin kHz QPOs. In contrast to the first case, SAX J1808.4À3658, the frequency separation Á between these kHz QPOs is consistent with the pulse frequency (190.6 Hz), not with half that value, confirming for the first time from pulsation measurements the inference, based on burst oscillations, that ''slow rotators'' … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
116
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(130 citation statements)
references
References 36 publications
13
116
0
1
Order By: Relevance
“…In XTEJ1807-294, the peak separation is consistent with the spin frequency (Linares et al 2005), and there generally appears to be a trend whereby the "slow" neutron stars have twin peaks with ∆ν ≈ ν s and the "fast" ones show ∆ν ≈ ν s (with the transition at about 300 Hz).…”
Section: Introductionsupporting
confidence: 55%
“…In XTEJ1807-294, the peak separation is consistent with the spin frequency (Linares et al 2005), and there generally appears to be a trend whereby the "slow" neutron stars have twin peaks with ∆ν ≈ ν s and the "fast" ones show ∆ν ≈ ν s (with the transition at about 300 Hz).…”
Section: Introductionsupporting
confidence: 55%
“…Campana et al (2003) observed the source during outburst with the XMM-Newton satellite at a luminosity level of about 2 × 10 36 erg s −1 (0.5−10 keV, assuming a distance of 8 kpc) with an X-ray featureless spectrum well fitted by an absorbed (N H ∼ 5 × 10 21 cm −2 ) blackbody plus hard Comptonization model like COMPTT (Titarchuk 1994). Kilohertz quasi-periodic oscilllations (kHz QPOs) have been detected in the X-ray flux of XTE J1807−294 during outburst with a frequency separation consistent with the 191 Hz pulse frequency (Linares et al 2005). From XMM-Newton outburst observations, Kirsch et al (2004) improved the determination of binary orbital parameters and estimated an X-ray mass function of the system of f X (M) = 1.6 × 10 −7 M , which implies (assuming a neutron star mass of 1.4 M and i = 90 • ) a minimum companion mass of 0.007 M .…”
Section: Xte J1807−294mentioning
confidence: 80%
“…At low frequencies where the relations are clearest, the match can be restored by multiplying the the upper and lower kHz QPO frequencies with ∼1.45, i.e., close to (but significantly different from) 1.5 . The millisecond pulsar XTE J1807-294 behaves in a similar way, but with a shift factor of ∼1.59 (Linares et al 2005). This suggests that the kHz QPOs form one group of correlated frequencies and the low frequency complex another, independent one.…”
Section: Relation Of Neutron Star Khz Qpos With Lower Frequency Phenomentioning
confidence: 78%
“…In their new model a beat interaction also plays a role, but now it occurs not at the inner edge, but at a resonant radius relatively far out, in the disk, where a resonant wave travels around the star at ν spin . In another millisecond pulsar, XTE J1807-294, twin kHz QPOs were found that have ∆ν ≈ ν spin = 191 Hz (Linares et al 2005); so, it seems very likely, as had been suspected earlier from oscillation frequencies measured during X-ray bursts, that the spin frequencies can be either ∼ ∆ν or ∼ 2∆ν. Fig.…”
Section: Kilohertz Quasi-periodic Oscillations and Orbital Motionmentioning
confidence: 82%